Bipolar Patterning of Polymer Membranes by Pyroelectrification. Issue 3 (19th November 2015) - Rega, Romina; Gennari, Oriella; Mecozzi, Laura; Grilli, Simonetta; Pagliarulo, Vito; Ferraro, Pietro
Abstract : Polymer freestanding membranes with permanent bipolar patterns are fabricated by "pyroelectrification". The thermal stimulation of periodically poled lithium niobate (PPLN) crystals simultaneously generates the pyroelectric effect, the glass transition of the polymer, and therefore the periodic electric poling of the polymer. The reliability of these membranes is demonstrated for applications under both dry and wet conditions, including cell patterning.